Large-scale experiment of a novel non-domestic building using BPSC systems for energy saving. (June 2020) - Paya-Marin, Miguel A.; Roy, Krishanu; Chen, Jian-Fei; Masood, Rehan; Lawson, R. Mark; Gupta, Bhaskar Sen; Lim, James B.P.
Abstract: The performance of a newly developed back pass non-perforated unglazed solar air collector (BPSC) is investigated in this paper for its thermal efficiency. BPSC is a cost-effective solar panel for new commercial buildings and industrial facades, which can be used as a main building wall or for the retrofitting of old buildings. BPSC provides a preheated air source for heating and ventilation, leading to a reduction in energy consumption. This study investigates the potential energy saving of a large scale non-domestic building that uses the BPSC system to provide pre-heated air for heating and ventilation. For this purpose, two identical buildings were constructed and tested at Kingspan R&D facilities in Kingscourt, Ireland. From the test results, it was found that the back pass solar air collector was able to reduce the heating load of the test buildings by approximately 20%. The most critical factors affecting the collector efficiency are air flow rate, collector height, and solar radiation. To enhance the performance of the BPSC system, it was assisted with a pre-heated air to water heat pump (AWHP) system. Finally, the performance of the BPSC, assisted with AWHP system was also evaluated experimentally, and it was found that an electricity savings of 36%, can be achieved through thermal energy efficiency of BPSC. Highlights: Thermal efficiency of the newly developed back pass non-perforated unglazed solar air collector (BPSC) is investigated. Potential energy saving of a large scale non-domestic building using BPSC system is studied. The back pass solar air collector was able to reduce the heating load of the test buildings by 20%. To enhance the performance of the BPSC system, it was assisted with a pre-heated air to water heat pump (AWHP) system.